Pengaruh Profitabilitas Terhadap Rasio Kecukupan Modal PadaBank Umum Persero Di Indonesia (Studi SelamaPandemi Covid-19) - Maharani Makom; Indriyani Pangestika (Strategic: Journal of Management Sciences, 2022)
This study aims to analyze the effect of Return On Assets (ROA), Return On Equity (ROE), and Net Interest Margin (NIM) on the Capital Adequacy Ratio (CAR) at Persero Commercial Banks in Indonesia during the Covid-19 Pandemic. The number of samples consists of 4 banks obtained by using total sampling technique. The data used in this study is secondary data sourced from the quarterly financial reports of Persero Commercial Banks, Indonesian Banking Statistics, and the official website of the Financial Services Authority (OJK). The data analysis model used is multiple linear regression analysis. F test results show that ROA, ROE, and NIM simultaneously have a significant effect on CAR. Based on the t test, the variable ROA, ROE, partially does not have a significant effect on CAR, while the NIM variable partially has a significant effect on CAR at Persero Commercial Banks in Indonesia..